Representasi Emosional Joker Sebagai Korban kekerasan Dalam Film Joker 2019 (Analisis Semiotika Ferdinand De Saussure) - Madhona, Rizkyka Hamama; Yenny (Soetomo Communication and Humanities, 2022)
This study aims to explain the emotional representation of the Joker as a victim of violence in the 2019 Joker film based on Ferdinand De Saussure's theory. Joker is a psychological thriller genre film. The film opens with Arthur Fleck trying out various expressions. With a clown-style make-up, Arthur pulled his face in a motion pulling the corners of his lips up to create a smiling facial expression. Arthur then lowered the corners of his lips down to make a sad expression with his lips down, and then pulled his lips back into a smile. A few tears flowed between her black eye makeup. The research method used in this paper is descriptive qualitative. This means that the data used in this study is qualitative data (data that does not consist of numbers) in the form of words and pictures that may be the key to what is being studied. Then the existing data are described from a number of aspects of signs or semiotics in a number of scenes. For example, from the emotional side that appears in a scene, the facial expressions of the actors, the dialogue delivered by the actors, background music and so on. Emotional representation is also shown through messages that are interpreted semiotically based on Ferdinand de Saussure's theory through changes in costumes (markers), from being originally monochrome (dark dominant) to being more colorful, and changes in a person's character from being closed to being more expressive in expressing their feelings sign).